Development and Investigation of a NASICON‐Type High‐Voltage Cathode Material for High‐Power Sodium‐Ion Batteries. Issue 6 (3rd January 2020) - Chen, Mingzhe; Hua, Weibo; Xiao, Jin; Cortie, David; Guo, Xiaodong; Wang, Enhui; Gu, Qinfen; Hu, Zhe; Indris, Sylvio; Wang, Xiao‐Lin; Chou, Shu‐Lei; Dou, Shi‐Xue
Abstract: Herein, we introduce a 4.0 V class high‐voltage cathode material with a newly recognized sodium superionic conductor (NASICON)‐type structure with cubic symmetry (space group P 21 3), Na3 V(PO3 )3 N. We synthesize an N‐doped graphene oxide‐wrapped Na3 V(PO3 )3 N composite with a uniform carbon coating layer, which shows excellent rate performance and outstanding cycling stability. Its air/water stability and all‐climate performance were carefully investigated. A near‐zero volume change (ca. 0.40 %) was observed for the first time based on in situ synchrotron X‐ray diffraction, and the in situ X‐ray absorption spectra revealed the V 3.2+ /V 4.2+ redox reaction with high reversibility. Its 3D sodium diffusion pathways were demonstrated with distinctive low energy barriers. Our results indicate that this high‐voltage NASICON‐type Na3 V(PO3 )3 N composite is a competitive cathode material for sodium‐ion batteries and will receive more attention and studies in the future. Abstract : A new NASICON‐type high‐voltage cathode material of Na3 V(PO3 )3 N was synthesized and its electrochemical performance was improved by carbon matrix decoration. An in‐depth investigation of the material was performed through in situ XAS and XRD, and its 3D sodium pathways were clearly identified through DFT calculations.